Changing patterns of human anthrax in Azerbaijan during the post-Soviet and preemptive livestock vaccination eras. - Ian Kracalik; Rakif Abdullayev; Kliment Asadov; Rita Ismayilova; Mehriban Baghirova; Narmin Ustun; Mazahir Shikhiyev; Aydin Talibzade; Jason K Blackburn (Public Library of Science (PLoS), 2014)
We assessed spatial and temporal changes in the occurrence of human anthrax in Azerbaijan during 1984 through 2010. Data on livestock outbreaks, vaccination efforts, and human anthrax incidence during Soviet governance, post-Soviet governance, preemptive livestock vaccination were analyzed. To evaluate changes in the spatio-temporal distribution of anthrax, we used a combination of spatial analysis, cluster detection, and weighted least squares segmented regression. Results indicated an annual percent change in incidence of (+)11.95% from 1984 to 1995 followed by declining rate of -35.24% after the initiation of livestock vaccination in 1996. Our findings also revealed geographic variation in the spatial distribution of reporting; cases were primarily concentrated in the west early in the study period and shifted eastward as time progressed. Over twenty years after the dissolution of the Soviet Union, the distribution of human anthrax in Azerbaijan has undergone marked changes. Despite decreases in the incidence of human anthrax, continued control measures in livestock are needed to mitigate its occurrence. The shifting patterns of human anthrax highlight the need for an integrated "One Health" approach that takes into account the changing geographic distribution of the disease.